Modeling and experimental research of the processes of formation of radiation damage in the interaction of gamma quantum flows and relativistic electron beams with solutions of organic dyes - Gokov, S.P.; Kazarinov, Yu.G.; Kalenik, S.A.; Kasilov, V.Y.; Kantemirov, V.V.; Mazilov, O.O.; Malykhina, T.V.; Tsiats’ko, V.V.; Tsiats’ko, E.V. (Вопросы атомной науки и техники, 2021)
The processes of interaction of an aqueous solution of an organic dye: methylene blue (MB) - C¹⁶H¹⁸N³SCl with gamma quanta and electrons were investigated. A model has been developed and the passage of electrons with an energy of 15 MeV through tungsten layers with a thickness of 1…8 mm has been simulated. Based on the simulation results, a number of experiments were carried out. Analysis of the calculated and experimental data showed that one incident electron destroys 4 times more dye molecules than one incident gamma quantum. Досліджено процеси взаємодії водного розчину органічного барвника: метиленового синього (МС) – C¹⁶H¹⁸N³SCl з гамма-квантами і електронами. Розроблено модель і змодельоване проходження електронів з енергією 15 МеВ через шари вольфраму товщиною 1…8 мм. Проведено ряд експериментів, заснованих на результатах моделювання. Аналіз розрахункових та експериментальних даних показав, що один падаючий електрон руйнує в 4 разів більше молекул барвника, ніж один падаючий гамма-квант. Исследованы процессы взаимодействия водного раствора органического красителя: метиленового синего (МС) – C¹⁶H¹⁸N³SCl с гамма-квантами и электронами. Разработана модель и смоделировано прохождение электронов с энергией 15 МэВ через слои вольфрама толщиной 1…8 мм. Проведен ряд экспериментов, основанных на результатах моделирования. Анализ расчетных и экспериментальных данных показал, что один падающий электрон разрушает в 4 раза больше молекул красителя, чем один падающий гамма-квант.